Genetic variation and molecular characterization of Zygophyllum coccineum L. ecotypes of the iron mining area of El-Wahat El-Bahariya in Egypt - El-Esawi, Mohamed A (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.